Communication from the executive of the commonwealth, transmitting a report from the adjutant general : in response to a resolution of the convention, calling for information concerning the militia and volunteers of the state, &c. (LLMC-digital (Series), 1861)
The Adjutant General's report of February 27, 1861 regarding the number and type of military forces in Virginia.